Genome-Wide Gene Expression Profiles in Antioxidant Pathways and Their Potential Sex Differences and Connections to Vitamin C in Mice - Jiao, Yan (Molecular Diversity Preservation International (MDPI), 2013)
Vitamin C (VC) is well known as an antioxidant in humans, primates and guinea pigs. Studies have suggested gender differences in VC requirements in humans, and gender differences in oxidant injury vulnerability in early life may represent a biological mechanism contributing to gender disparity in later life. Using spontaneous bone fracture (sfx) mice, which lack the gene for L-Gulonolactone oxidase (Gulo), we studied the potential sex difference in expression profiles of oxidative genes at the whole-genome level. Then, we analyzed data of gene expressions in a mouse population of recombinant inbred (RI) strains originally derived by crossing C57BL/6J (B6) and DBA/2J (D2) mice. Our data indicated that there were sex differences in the regulation of pre- and pro-oxidative genes in sfx mice. The associations of expression levels among Gulo, its partner genes and oxidative genes in the BXD (B6 × D2) RI strains showed a sex difference. Transcriptome mapping suggests that Gulo was regulated differently between female and male mice in BXD RI strains. Our study indicates the importance of investigating sex differences in Gulo and its oxidative function by using available mouse models.